XANTHINE OXYDASE INHIBITION OF KOMBUCHA TEA IN HYPERURICEMIA INDUCED WISTAR RAT: decrease of uric acid, malondialdehyde, and 8-hydroxy-2'-deoxyguanosine - Sukrama, I Dewa Made (BALI MEDICAL JOURNAL, 2015)
Background: Hyperuricemia is a condition of high level of uric acid in the body due to distortion of purine nucleoside metabolism through hipoxanthin, xanthin, and guanin of basic purine. Objective: to find a cure of hyperuricemia base on the utilization of kombucha tea. Methods: This is a true experimental study by applying posttest only control group design to determine whether kombucha tea inhibit xanthine oxidase in hyperuricemic induced rat reveales by decrease of uric acid, malondialdehyde (MDA), and 8-hydroxy-2’-deoxyguanosine (8-OHdG). In this study, hyperuricemia rat was achieved by intake of high purine diet. Rats were fed with a mixture of 4 g/kg BW of Gnetum gnemon with 50 mL/kg BW of chicken liver ad libitum for 9 days. Treatments in this research are combination of fermentation time of Kombucha tea and volume of this tea, i.e fermentation time 4, 8, and 12 days and the volume are 1 mL and 4 mL. Therefore, there would be seven groups of treatment including control group. ANOVA was then applied to determine the treatment effect with p < 0.05 was concidered significant. Results: This study indicates that kombucha tea has an ability to inhibit xanthine oxidase in hyperuricemic induced rat and decrease uric acid, MDA, and 8-OHdG. This ability was achieved with combination treatment of 12 days fermentation and 4 mL of kombucha intake. Xanthine oxidase, uric acid, MDA, and 8-OHdG levels by this treatment were obtained significantly lower compare to control group. Conclusion: This study proved that kombucha tea was potent to cure hyperuricemia of wistar rat via inhibition of xanthine oxidase produced.